2020
DOI: 10.1177/2053951720935616
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of good data management: Findings from a UK-based survey

Abstract: Low levels of public trust in data practices have led to growing calls for changes to data-driven systems, and in the EU, the General Data Protection Regulation provides a legal motivation for such changes. Data management is a vital component of data-driven systems, but what constitutes ‘good’ data management is not straightforward. Academic attention is turning to the question of what ‘good data’ might look like more generally, but public views are absent from these debates. This paper addresses this gap, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…• data trusts, in which the intermediary will take on responsibility to steward supplier data for agreed purposes. Data trusts may be based on fiduciary duties to act in the suppliers' interests (Edwards, 2004;Hall & Pesenti, 2017;O'Hara, 2019;Delacroix & Lawrence, 2019; GPAI/Aapti/ODI 2021), and/or be based on a contractual or statutory legal obligations (ODI, 2018;Reed et al, 2019;Ada Lovelace, 2021; GPAI/Aapti/ODI 2021); • data commons, with members voluntarily 'pooling' their data for the benefit of a specific community (Wong & Henderson, 2020;Hartman et al 2020), or for the general public interest Data Governance Act; • data cooperatives, often referring to a data intermediary owned and democratically controlled by its members who delegate control over data about them (Hartman et al, 2020); • data collaboratives, where participants from different sectors -including private companies, research institutions, and government agencies -can exchange data and data expertise to help solve public problems (S.…”
Section: Terminologiesmentioning
confidence: 99%
“…• data trusts, in which the intermediary will take on responsibility to steward supplier data for agreed purposes. Data trusts may be based on fiduciary duties to act in the suppliers' interests (Edwards, 2004;Hall & Pesenti, 2017;O'Hara, 2019;Delacroix & Lawrence, 2019; GPAI/Aapti/ODI 2021), and/or be based on a contractual or statutory legal obligations (ODI, 2018;Reed et al, 2019;Ada Lovelace, 2021; GPAI/Aapti/ODI 2021); • data commons, with members voluntarily 'pooling' their data for the benefit of a specific community (Wong & Henderson, 2020;Hartman et al 2020), or for the general public interest Data Governance Act; • data cooperatives, often referring to a data intermediary owned and democratically controlled by its members who delegate control over data about them (Hartman et al, 2020); • data collaboratives, where participants from different sectors -including private companies, research institutions, and government agencies -can exchange data and data expertise to help solve public problems (S.…”
Section: Terminologiesmentioning
confidence: 99%
“…The use of telematics devices implies monitoring and recording customers' behaviour. It has been shown that consumers are less likely to consent to share their data when it is accessible to companies (Hartman et al, 2020). While access to driving data has been less hotly debated than health data (Cheung, 2020), the revolution promised by Big Data may also be hindered by customer reluctance.…”
Section: M2 Moral and Political Preventionsmentioning
confidence: 99%
“…That is not to say that citizens have no clear expectations towards datafication. To the contrary, recent findings imply that users want more control and accountability ( Hartman et al, 2020 ); but experts need to listen closer to these demands and engage in dialogues with the public about perceived risks.…”
Section: The Urgency For Data Literacymentioning
confidence: 99%